PENGARUH HERBISIDA ISOPROPILAMINA GLIFOSAT TERHADAP FEKUNDITAS DAN VIABILITAS KOKON CACING TANAH Pontoscolex corethrurus Fr. Mull. - Madani, Indra; Sumarmin, Ramadhan; Indriati, Gustina (Pendidikan Biologi, 2013)
ABSTRACTThe use of herbicides had the adverse impact on non-target organisms being one of the soil biota such as earthworms. One of the herbicide is glyphosate isopropylamine. The aimed of this study to know the influence of Isopropylamine Glyphosate Herbicides to fecundity and viability Earthworm Cocoon (Pontoscolex corethrurus Fr. Mull.). This study was conducted in July-August, 2013, held at the Zoology Laboratory of the Biology Department, Padang State University. This research used Completely Randomized Design (CRD) with 5 treatment, 5 replicates. The treatment were herbicide glyphosate isopropylamine of 0% (A), 0.1% (B), 0.2% (C), 0.3% (D) and 0.4% (E) mixed media. Parameters in this study is the fecundity and viability of earthworm cocoons Pontoscolex corethrurus. The results showed. the average number of cocoons on providing the highest herbicide isopropylamine glyphosate on A (40) and followed by B and C are 14.6 cocoon, D (14.2) and the lowest in the herbicide glyphosate isopropylamine E are 0 cocoon. While the average percentage hatchability earthworm cocoons Pontoscolex corethrurus on providing the highest herbicide glyphosate isopropylamine A, B and C was 100% and the lowest concentrations of D and E are 0%. It can be concluded that the herbicide glyphosate isopropylamine can decrease fecundity cocoon, but had no effect on the viability of cocoons. Based on it, the civil must, to reduce the use of chemical herbicides cause poor soil.Â